Introduce Characteristic, Types and Functional Mechanism of Adjuvants as a Biologic Complement - Tahereh Zarei Taher; Ali Kowsari; Mohsen Sheykhhasan; Hamed Manoochehri; Naser Kalhor; Leila Naserpour (Fasa University of Medical Sciences, 2019)
The widespread use of effective vaccines against infectious diseases has been one of the most important public health progresses in the 21st century. Early vaccines containing weakened or inactivated pathogens or toxins may elicit robust, protective immune responses, but this approach cannot always be used because it is impractical and inefficient to culture large numbers of organisms, and lack of safety. In such cases subunits (e.g., microbial proteins or carbohydrate) are being considered as vaccine antigens. Since the subtypes of antigens often have weak immunogenic properties, they cannot stimulate the innate immune system. This property is probably the cause of the reduced efficacy of the vaccine. Adjuvants are molecules, compounds, or supramolecular complexes that boost the potency and longevity of specific immune response to antigens, but can cause minimal toxicity or long-lasting immune effects on human. Adjuvants can be used to enhance immunogenicity, modulate the type of immune response, reduce the amount of antigen or the number of immunizations required for efficacy, and/or improve the efficacy of vaccines in specific populations (e.g., newborns or elderly). The present paper reviews the different types of adjuvants and examines the characteristics and mechanisms of their performance.